'A crooked, passion-laden mirror': 'Jews' and 'Muslims' as a European question beyond religio-secularism. (14th March 2020) - Jansen, Yolande
ABSTRACT: In this article, Jansen attempts to demonstrate that addressing the religious practices of Jews and Muslims from the perspective of a religio-secular framework in today's European context underestimates the complexity of semiotic relations between Muslims, Jews and other Europeans. She discusses this complexity in terms of 'intercultural semiotics' between the three groups. In particular, she focuses on what she calls 'mirroring relations', drawing on an expression from Yirmiyahu Yovel about a 'crooked, passion-laden mirror' characterizing the ways in which modern Europeans imagined their Jewish neighbours in early twentieth-century Europe. In order to further explain this, Jansen analyses a passage from Marcel Proust's novel In Search of Lost Time, which concerns a group of people in late nineteenth-century France, following the Dreyfus Affair, who are perceived by the narrator as Jewish. Thereafter, drawing on Gil Hochberg's notion of the 're-membering' of the Semite, Jansen analyses semiotic mirroring in the work Projet Deburkanisation (2017) by the Belgian author Rachida Lamrabet, which she reads as a contemporary meta-reflection, involving Muslims, on the mirroring relations between Jews and other Europeans first discussed via her reading of Proust.